Thyroid Autoantibodies do not Impair the Ovarian Reserve in Euthyroid Infertile Women: A Cross-Sectional Study - Osuka, Satoko; Iwase, Akira; Goto, Maki; Takikawa, Sachiko; Nakamura, Tomoko; Murase, Tomohiko; Kato, Nao; Bayasula; Kotani, Tomomi; Kikkawa, Fumitaka (Hormone and Metabolic Research, 2018)
Patients with primary ovarian insufficiency (POI) have a high prevalence of thyroid autoimmune disorders. However, the extent of the contribution of thyroid autoantibodies or elevated thyroid-stimulating hormone (TSH) levels to decreased ovarian reserve is unclear. Therefore, we evaluated the serum levels of anti-Müllerian hormone (AMH) and thyroid autoantibodies [antithyroperoxidase antibody (TPOAb), and antithyroglobulin antibody (TgAb)] in euthyroid infertile women. One hundred and fifty-three women with normal menstrual cycles were recruited for this retrospective study. Serum levels of AMH were compared between patients with positive and negative thyroid autoantibodies. The correlation between serum levels of AMH and each thyroid autoantibody was also evaluated. Participants were observed to be either TPOAb or TgAb positive (n=27), only TPOAb positive (n=8), only TgAb positive (n=7), TPOAb and TgAb positive (double positive; n=12), and TPOAb and TgAb negative (double negative; n=126). No significant differences were found in serum AMH levels between the TPOAb- or TgAb-positive women and the antibody-double negative women. Serum AMH levels did not show a significant correlation with the concentration of TgAb or TPOAb. On the other hand, serum AMH levels negatively correlated with TSH levels in patients who were either positive for TPOAb or TgAb. Thyroid autoantibodies are not likely to influence ovarian reserve in euthyroid women whose TSH levels fall within the normal range although elevated TSH levels may be involved in the decline of serum AMH levels.
Keywords: anti-Müllerian hormone; infertility; ovarian reserve; primary ovarian insufficiency; thyroid autoantibody